Financial Intermediation, Investment Dynamics, and Business Cycle Fluctuations - Ajello, Andrea (American Economic Review, 2016)
I use micro data to quantify key features of US firm financing. In particular, I establish that a substantial 35 percent of firms' investment is funded using financial markets. I then construct a dynamic equilibrium model that matches these features and fit the model to business cycle data using Bayesian methods. In the model, financial intermediaries enable trades of financial assets, directing funds toward investment opportunities, and charge an intermediation spread to cover their costs. According to the model estimation, exogenous shocks to the intermediation spread explain 25 percent of GDP and 30 percent of investment volatility. (JEL D22, D92, E32, G21, G31, G32)